121k views
2 votes
Help me please I can't get the final step​

Help me please I can't get the final step​-example-1
User Jamal Aziz
by
5.4k points

1 Answer

3 votes

Answer:


\displaystyle m=(2)/(3),\ n=(4)/(3)

Step-by-step explanation:

Dimensional Analysis

It's given the relation between quantities A, B, and C as follows:


\displaystyle A=(3)/(2)B^mC^n

and the dimensions of each variable is:


A=L^2T^2


B=LT^(-1)


C=LT^2

Substituting the dimensions into the relation (the coefficient is not important in dimension analysis):


\displaystyle L^2T^2=\left(LT^(-1)\right)^m\left(LT^2\right)^n

Operating:


L^2T^2=\left(L^mT^(-m)\right)\left(L^nT^(2n)\right)


L^2T^2=L^(m+m)T^(-m+2n)

Equating the exponents:


m+n=2


-m+2n=2

Adding both equations:


3n=4

Solving:


n=4/3


m=2-4/3=2/3

Answer:


\mathbf{\displaystyle m=(2)/(3),\ n=(4)/(3)}

User Stephen Chu
by
5.4k points